Critical Literacy: Beyond Reading and Writing in the Bahamian Tertiary Classroom - Sairsingh, Marie (International Journal of Bahamian Studies, 2017)
Critical literacy can be defined as a cluster of specialized skills and competencies that facilitate an intensely engaged way of interpreting our world through careful textual and discursive analyses. It involves understanding the processes of learning to read and write as the precursor to a heightened awareness of one’s location within specific power relations, as well as its importance to ensuring a sustainable democracy. Ultimately, critical literacy is an indispensable component of the broader literacy mandate at the University of The Bahamas, as it can propel students toward greater participation in national discourse, and ultimately, toward meaningful social transformation. While this paper presents anecdotal rather than analytic evidence of students’ growth toward increased critical intelligence, it provides significant insight into the processes of their intellectual growth.